Muhammad Abduh’s contributions to modernity - Amir, Ahmad N.; Shuriye, Abdi Omar; Ismail, Ahmad Faris (Leena & Luna International, Oyama, Japan, 2012)
This paper analyzes the contributions of Shaykh Muhammad ‘Abduh to modernity, and his struggle for change and reform in al-Azhar and Egyptian society. Abduh was hailed as the “first leader of modern thought in Egypt”, “the father of the 20th century Muslim thought” and “pioneers of the modernist movement in the Arab world”, whose legacy in the history of Islamic reform was significant, carrying dynamic role in the transformation and reinterpretation of Islam in contemporary thought. His contribution to Islamic modernism was clearly seen in liberalizing the educational system, restructuring the mufti (jurist consult) office, transforming the Islamic worldview, championing Islamic feminism and integrating western and Islamic ideals and tradition.